METHODOLOGY FOR EVALUATING THE QUALITY OF THE PREDICTIONS OF CONSUMER DEMAND AND VOLUMES OF MINERAL-RAW MATERIAL RESOURCES PRODUCTION - Galiyeva A.K; Toksanova A.N; Ukubassova G.S; Abildina A.Sh; aalimbaeva@mail.ru (Academic Journal of Physical and Chemical Sciences, 2019)
The aim of the article is to develop theoretical and methodological foundations for improving consumer demand forecasting and the volume of mineral resources production гтвук modern conditions in order to identify priority areas for the mining industry development. The paper reveals the role and importance of forecasting for consumer demand and the volume of production of mineral resources and identifies deficiencies in forecasting, reducing the forecasts quality. As recommendations for improving the forecasting of consumer demand and the volume of mineral resources production, the multi-criteria economic and mathematical models developed by the authors are proposed for forecasting the volume of mineral resources production, taking into account the consumer demand. The value of work for economic science is that the forecasting of demand and production volumes is considered in its close relationship. The practical significance of the work lies in the possibility of applying a set of models for economic forecasting of demand and production volumes of mineral resources under the modern conditions.